Obstetric Outcomes in U.S. Veterans: Emerging Knowledge, Considerations, and Gaps - Hugin, Michele; Shaw, Jonathan G. (Seminars in Reproductive Medicine, 2019)
In the post-9/11 era, the number of young women serving, and deploying, in the military grew rapidly; as they exit service, there is tremendous increase in reproductive-aged women Veterans. Here, we review the limited but growing research regarding Veterans' pregnancy and obstetric outcomes. U.S. women Veterans returning from deployment carry a high burden of physical and mental health conditions, and often trauma. As poor mental health is known to predict poorer maternal and infant sequelae, there are unique concerns around perinatal outcomes in Veterans. Accordingly, there is new attention to their reproductive risks and needs—evidenced by recent research and programmatic efforts within the VA. Emerging research suggests that the unique health profiles of pregnant Veterans, including prevalent posttraumatic stress disorder, predict increased risk of preterm birth, preeclampsia, and gestational diabetes. In the most contemporary large study, relying on California birth data, Veterans who relied on VA for their health care coverage were high risk, with increased rates of preeclampsia and Cesarean delivery. Additionally, Veterans' infants (compared with non-Veterans') were more likely to require NICU care. Additional research is needed to explore upstream factors leading to these poorer outcomes. Current effort to coordinate VA and non-VA care for Veteran mothers is warranted.
Keywords: Veterans; pregnancy; perinatal